Zanim nastolatek zacznie zmieniać świat. Przedsiębiorczość nastolatków (adolescent entrepreneurship) – systematyczny przegląd literatury - Grzegorz Simborowski (Studia i Materiały, 2021)
Adolescence is a period of heightened search for one’s identity and formation of one’s psychosocial self. Is this significantly different from entrepreneurial experimentation and identification of market opportunities? The main goal of this systematic literature review was to discover the existing body of knowledge about adolescent entrepreneurship, to identify a potential research gap, and to identify existing trends. The result indicates that in the eyes of most researchers, entrepreneurship has nothing in common with the joyful process of creating something new without looking at the resources available. They try to convince us that adolescents need to be prepared for entrepreneurship – properly nurtured, shaped and educated.